Subsidence history, gravity anomalies, and flexure of the northeast Australian margin in Papua New Guinea - Haddad, D; Watts, A (1999)
Gravity and well data have been used to model the foreland basin flanking the Papua New Guinea orogenic belt. Backstripping of sediments from well data reveals a former passive margin that has probably experienced at least two major orogenic loading events. The first of these took place at or near the Miocene-Oligocene boundary and was associated with widespread carbonate deposition across the existing shelf and evolving basin. The second event is most likely related to the start of the main phase of uplift in the fold-and-thrust belt near the beginning of the Pliocene. Sedimentation in the Papuan Basin altered from a system dominated by carbonate accumulation to one of rapid deposition of terrigenous clastic sediments shed from the emerging orogen. For the purposes of gravity and flexure modeling, the base of the foreland sequence was defined as a horizontal surface that existed at the time of the initial collision. A total of seven gravity, topography, and stratigraphic profiles were constructed and used to model the flexure of the lithosphere supporting the onshore Papuan Basin and New Guinea orogen. The best fit model was a semi-infinite elastic plate in which the plate break was located approximately midway across the orogenic belt. The elastic plate thickness T(e) was found to be high in the western regions of Papua New Guinea (T(e) of 70-80 km) with little variation across the first four profiles, but it weakened considerably to the east where T(e) varied rapidly from 60 km to as little as 8 km. This sudden weakening of the lithosphere occurred as a narrow zone at the foot of the mountain belt. The weakening could be related to a low-strength zone within the former margin. Alternatively, it reflects the western extent of late Tertiary volcanism that was produced by the subduction of the Solomon Sea Plate beneath Australia.